Produksi Tepung Tulang Ikan Tuna (Thunnus Sp) Dengan Metode Kering Sebagai Sumber Kalsium Dan Fosfor Untuk Pembuatan Biskuit - W, SUARSA I; A.A, BAWA PUTRA; SANTI, SRI RAHAYU; FARUK, ABDUL (Jurnal Ilmu Pendidikan Indonesia, 2020)
Research has been conducted on processing tuna bones into flour which has a high mineral content which aims to produce nutritious biscuits in the form of food products. This study obtained the results that the tuna bone water content was 6.40% and the biscuit water content was 2.67%, the calcium and phosphorus content of tuna fish was 5.35% and 3.37%, while the biscuit dough with variations in the ratio between flour and fish bones namely 100 : 0; 95 : 5; 90 : 10; and 85 : 15 obtained the results of increased calcium content of 0.9%; 0.97%; 1.25%; and 1.29%; and phosphorus content 0.38%; 0.43%; 0.46%; and 0.60%; and the protein content is 9.32%; 11.74%; 11.99%; and 12.4